Analisis Motivasi, Gaya kepemimpinan Demokratis, dan Lingkungan Kerja Dalam Meningkatkan Kinerja Karyawan CV Teguh Karya Mandiri - Achmad Rifani Rahmatulloh; Supardi Supardi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of work motivation, democratic leadership style, and work environment on employee performance at CV Teguh Karya Mandiri. The research applies a quantitative approach with an associative research design to examine the relationships among the variables. The sampling technique used was a saturated sample, involving 70 employees as respondents. Data were collected through questionnaires using a five-point Likert scale. The data analysis method employed was Structural Equation Modeling–Partial Least Square (SEM-PLS) using SmartPLS software. The results indicate that work motivation has a positive and significant effect on employee performance. Democratic leadership style also shows a positive and significant influence on improving employee performance. Furthermore, a safe and comfortable work environment supported by adequate facilities contributes positively and significantly to employee performance. Simultaneously, these three variables significantly contribute to enhancing employee performance. The findings of this study are expected to provide practical insights for companies in improving human resource management to achieve more optimal and sustainable work productivity.